Multi-site Pain Is Associated with Long-term Patient-Reported Outcomes in Older Adults with Persistent Back Pain. Issue 10 (5th January 2019) - Rundell, Sean D; Patel, Kushang V; Krook, Melissa A; Heagerty, Patrick J; Suri, Pradeep; Friedly, Janna L; Turner, Judith A; Deyo, Richard A; Bauer, Zoya; Nerenz, David R; Avins, Andrew L; Nedeljkovic, Srdjan S; et al.
Abstract: Objective: To estimate the prevalence of co-occurring pain sites among older adults with persistent back pain and associations of multisite pain with longitudinal outcomes. Design: Secondary analysis of a cohort study. Setting: Three integrated health systems in the United States. Subjects: Eight hundred ninety-nine older adults with persistent back pain. Methods: Participants reported pain in the following sites: stomach, arms/legs/joints, headaches, neck, pelvis/groin, and widespread pain. Over 18 months, we measured back-related disability (Roland Morris, scored 0–24), pain intensity (11-point numerical rating scale), health-related quality of life (EuroQol-5D [EQ-5D], utility from 0–1), and falls in the past three weeks. We used mixed-effects models to test the association of number and type of pain sites with each outcome. Results: Nearly all (N = 839, 93%) respondents reported at least one additional pain site. There were 216 (24%) with one additional site and 623 (69%) with multiple additional sites. The most prevalent comorbid pain site was the arms/legs/joints (N = 801, 89.1%). Adjusted mixed-effects models showed that for every additional pain site, RMDQ worsened by 0.65 points (95% confidence interval [CI] = 0.43 to 0.86), back pain intensity increased by 0.14 points (95% CI = 0.07 to 0.22), EQ-5D worsened by 0.012 points (95% CI = –0.018 to –0.006), and the odds of falling increased by 27% (odds ratio = 1.27, 95% CI = 1.12 to 1.43). Some specific pain sites (extremity pain, widespread pain, and pelvis/groin pain) were associated with greater long-term disability. Conclusions: Multisite pain is common among older adults with persistent back pain. Number of pain sites was associated with all outcomes; individual pain sites were less consistently associated with outcomes.